1997
DOI: 10.1017/s0790966700003189
|View full text |Cite
|
Sign up to set email alerts
|

Community and hospital residential care: a comparative evaluation

Abstract: Objective: To compare the quality of care offered by a community hospital hostel and three hospital rehabilitation facilities (two traditional rehabilitation wards and an innovative normalisation unit) for people with longterm mental illnesses.Method: Quality of care is assessed here on three different levels: those of Input using Programme Analysis of Service Systems; Assessment of Care Environments; Process using Ward Management Practices Questionnaire; Attitudes to Treatment Questionnaire; Outcome using Reh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Perkins and Dilks (1992) commented on how symptom and identity problems made it very hard for mental health professionals to establish working relationships with service users. Quality of life research conducted by Jerome and colleagues showed an additional "gulf" between people who provided mental health services and those who used them (Carson et al, 1997;Missenden et al, 1996). More recently Rosie Allen and colleagues have shown significant differences in flourishing between people with mental health problems and community groups (Allen et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Perkins and Dilks (1992) commented on how symptom and identity problems made it very hard for mental health professionals to establish working relationships with service users. Quality of life research conducted by Jerome and colleagues showed an additional "gulf" between people who provided mental health services and those who used them (Carson et al, 1997;Missenden et al, 1996). More recently Rosie Allen and colleagues have shown significant differences in flourishing between people with mental health problems and community groups (Allen et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…It always struck the second author that there were more differences than just symptoms and identity between professionals and service users, and that in many ways each group inhabited different worlds. Comparisons between staff and service users also showed that quality of life was markedly different between the two groups (Carson et al, 1997;Missenden et al, 1996). Towards the end of the 20th century, recovery became the dominant model in mental health services and many professionals starting working in partnership with service users, inspired by individuals like Bill Anthony, Geoff Shepherd, Patricia Deegan, Mike Slade, Peter Bullimore and Rachel Perkins, to name but a few pioneers.…”
Section: Introductionmentioning
confidence: 99%